Postpartum amenorrhea duration by sex of the newborn in two natural fertility populations. Issue 4 (12th December 2020) - Hoi, Amber Gigi; Daiy, Katherine; Altman, Rachel MacKay; Venners, Scott; Valeggia, Claudia; Nepomnaschy, Pablo
Abstract: Objectives: Postpartum amenorrhea (PA) affects the length of interbirth intervals and thus is intimately related to human life history strategies. PA duration appears to be influenced by maternal energetic status. In humans, as in other mammals, sons are costlier than daughters. Thus, we hypothesize that, in energetically constrained environments, a newborn's sex should be associated with PA duration. Methods: We analyzed data from two natural fertility populations in which mothers have differing energy budgets: Qom women (n = 121) from a periurban village in Argentina, who have a comparatively calorically dense diet and are sedentary (prepregnancy mean BMI = 24.8 ± 4.5 kg/m 2 in 1997), and agropastoral Kaqchikel Maya women (n = 88), who have a comparatively calorically restricted diet and high physical activity levels (mean BMI = 21.8 ± 3.7 kg/m 2 ). We predict that (a) mothers of sons exhibit longer PA duration than mothers of daughters and (b) this association between offspring sex and PA duration is stronger in the Maya, who have smaller energy budgets. Results: Maya mothers with sons exhibited estimated mean and median PA durations that were 1.34 times the estimated mean and median PA duration of mothers with daughters ( p = 0.02). Among the Qom, mean, and median PA duration did not differ significantly in relation to offspring sex ( p = 0.94). Conclusions: Maya mothers with sons exhibited longer PA duration than those with daughters. This phenomenon was not observed in the well‐nourished Qom, possibly due to "buffering" effects from larger energy budgets. Offspring sex may influence birth spacing and maternal life history strategies in energetically constrained environments.